A study of the onset of burnout in sports: Development of an athlete version of the burnout process questionnaire - Tanaka,T.; Susaki, Y.; Mizuochi, F.; Sugiyama, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2016)
The present study was conducted to establish an Athlete Version of the Burnout Process Questionnaire (ABPQ) in order to evaluate the adaptation of "enthusiasm", "stagnation", "clinging to sport", and "exhaustion" to the clinical psychology model (study 1), and to examine the validity of the resulting model in terms of the relationship between each state and burnout (study 2). In study 1, 432 university athletes (males=303, females=129) participated. A face sheet and the draft ABPQ were used. The results of factor analysis related 4 factors —"enthusiasm", "stagnation", "clinging to sport", and "exhaustion"— with 20 items in the clinical psychology model. In addition, the reliability and validity of this ABPQ scale were confirmed. In study 2, 303 university male athletes participated. A face sheet, the ABPQ and the Athletic Burnout Inventory (ABI) were used. Firstly, we established a verification model based on the clinical psychology model. Set "enthusiasm" as an independent variable, which was evaluated by the ABPQ, "stagnation", "clinging to sport", and "exhaustion" as mediators, and burnout as a dependent variable, evaluated by the ABI. Moreover, path analysis was used to examine the validity of the model and the relationship between each state and burnout. The validity of the clinical psychology model was confirmed (GFI=.916, AGFI=.893, CFI=.938, RMSEA=.056). In addition, the relationship between each state and burnout in the process of burnout onset was elucidated.